2020
DOI: 10.1038/s41467-020-16507-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal networks maintain local dominance of ectomycorrhizal trees

Abstract: The mechanisms regulating community composition and local dominance of trees in species-rich forests are poorly resolved, but the importance of interactions with soil microbes is increasingly acknowledged. Here, we show that tree seedlings that interact via root-associated fungal hyphae with soils beneath neighbouring adult trees grow faster and have greater survival than seedlings that are isolated from external fungal mycelia, but these effects are observed for species possessing ectomycorrhizas (ECM) and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 47 publications
4
105
0
2
Order By: Relevance
“…As predicted, AM tree species showed a stronger CNDD effect than did ECM tree species across these temperate forests. This result is partly in line with a recent plant-soil feedback experiment that finds ECM tree species show positive feedback and AM tree species negative feedback (Bennett et al 2017), and the findings from natural forests that CNDD of AM tree species is stronger than ECM tree species (Chen et al 2019, Jiang et al 2020, Liang et al 2020. However, our study provided evidence that this pattern might be generalizable across temperate forests at a broad spatial scale.…”
Section: Different Cndd Strength Between Am and Ecm Tree Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…As predicted, AM tree species showed a stronger CNDD effect than did ECM tree species across these temperate forests. This result is partly in line with a recent plant-soil feedback experiment that finds ECM tree species show positive feedback and AM tree species negative feedback (Bennett et al 2017), and the findings from natural forests that CNDD of AM tree species is stronger than ECM tree species (Chen et al 2019, Jiang et al 2020, Liang et al 2020. However, our study provided evidence that this pattern might be generalizable across temperate forests at a broad spatial scale.…”
Section: Different Cndd Strength Between Am and Ecm Tree Speciessupporting
confidence: 92%
“…Although the colonization of AM fungi can diminish the CNDD on tree performance (Liang et al 2015), the positive effect is more prominent for ECM compared to AM fungi. Supporting this hypothesis, recent studies found that using fungicide and removing fungal hyphae showed a stronger negative influence on the growth and survival of ECM than AM tree species (Jia et al 2020, Liang et al 2020). Multiple factors can contribute to the weaker CNDD of ECM tree species.…”
Section: Discussionmentioning
confidence: 90%
“…The four heterospecifics represent common ectomycorrhizal trees that co‐occur with Q. rubra in this area. Tree species that associate with ectomycorrhizal fungi typically exhibit weaker CNDD (Brown et al 2019, Jiang et al 2020) or sometimes exhibit positive effects on their nearby seedlings by sharing a common mycelial network (Teste et al 2009, Liang et al 2020). Additionally, the strength and direction of feedbacks for an individual species can differ depending on whether the heterospecifics are of the same or different mycorrhizal type (Kadowaki et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…For example, seedlings typically exhibit greater overall mortality (Walters and Reich 1996) and stronger effects of CNDD (McCarthy‐Neumann and Ibáñez 2013) in low light conditions. Recently, studies have suggested that the response of seedlings to density‐dependent effects may also depend on the type of mycorrhizal fungi with which they associate, as ectomycorrhizal species typically exhibit less negative, or even positive, effects from neighboring conspecifics (Bennett et al 2017, Kadowaki et al 2018, Jiang et al 2020, Liang et al 2020). Seedling size may also play a role: Smaller seedlings are likely younger, and seedlings are most vulnerable to herbivory and infection from pathogens in their earliest stages of development (Kitajima and Fenner 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Ectomycorrhizal (ECM) fungi can also protect their hosts from pathogens and are thought to provide better protection against pathogens than AM fungi because of the sheath, hyphal network, and antimicrobial substances associated with ECM fungi (Garrett 1956;Marx 1972;Stack 1975;Duchesne et al 1989). Evidence has been accumulating to suggest that ECM fungal protection against soil-borne pathogens can be a major mechanism behind more positive plant-soil feedbacks among ECM driving mono-specific stands of ECM compared to AM species (Connell & Lowman 1989;Laliberte et al 2015;Liang et al 2020). These findings suggest that ECM invasive plants may be less susceptible to pathogens than AM or non-mycorrhizal invaders, provided they encounter compatible ECM fungi.…”
Section: Root Traitsmentioning
confidence: 99%